Representasi Keselamatan dalam Iklan Gojek “It’s Okay to be Lebay” (Analisis Semiotika Charles Sanders Pierce) - Carissa Honouris; Gregorius Genep Sukendro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The study aims to find out how the representation of safety contained in Gojek's